3D printing characteristics and mechanical properties of a bio scaffold obtained from a Micro-CT Scan, using the fused deposition modeling technique = Características de la impresión 3D y propiedades mecánicas de un bioandamio generado a partir de un Micro-CT Scan, utilizando la técnica de modelado por deposición fundida - González Sánchez, Natalia María 1996-
The objective is to determine which biopolymer has the best 3D printing characteristics and mechanical properties for the manufacture of a bioscaffold, using the fused deposition printing technique, with models generated from an STL file obtained from a Micro-CT scan taken from a bovine iliac crest bone structure. Through an experimental exploratory study, three study groups of the analyzed biopolymers were carried out with thirteen printed structures of each one. The first is made of 100% PLA. The second, 90B, we added 1g of diatom extract, and the third, 88C, differs from the previous one in that it also contains 1g of calcium phosphate. The 39 printed structures underwent a visual inspection test, which required the fabrication of a gold standard scaffold in resin, with greater detail and similarity to the scanned bone structure. Finally, the structures were subjected to a compressive force (N) to obtain the modulus of elasticity (MPa) and compressive strength (MPa) of each one of them. A statistically significant difference (p=0.001) was obtained in the printing properties of the biomaterial 88C, compared to 90B and pure PLA and the 88C presented the best 3D printing characteristics. In addition, it also presented the best mechanical properties compared to the other groups of materials. Although the difference between these was not statistically significant (p=0.388), in the structures of the 88C biomaterial, values of compressive strength (8,84692 MPa) and modulus of elasticity (43,23615 MPa) were similar to those of cancellous bone in the jaws could be observed. Because of this result, the 88C biomaterial has the potential to be used in the manufacture of bioscaffolds in tissue engineering.